Two years of pulsar observations with the ultra-wide-band receiver on the Parkes radio telescope. Issue 1 (16th January 2021) - Johnston, Simon; Sobey, C; Dai, S; Keith, M; Kerr, M; Manchester, R N; Oswald, L S; Parthasarathy, A; Shannon, R M; Weltevrede, P
ABSTRACT: The major programme for observing young, non-recycled pulsars with the Parkes telescope has transitioned from a narrow-band system to an ultra-wide-band system capable of observing between 704 and 4032 MHz. We report here on the initial 2 yr of observations with this receiver. Results include dispersion measure (DM) and Faraday rotation measure (RM) variability with time, determined with higher precision than hitherto, flux density measurements and the discovery of several nulling and mode changing pulsars. PSR J1703−4851 is shown to be one of a small subclass of pulsars that has a weak and a strong mode which alternate rapidly in time. PSR J1114−6100 has the fourth highest |RM| of any known pulsar despite its location far from the Galactic Centre. PSR J1825−1446 shows variations in both DM and RM likely due to its motion behind a foreground supernova remnant.